Analysis of market current state and historical roots of ice wine production - Ostapenko, Viktoria; Tkachenko, Oksana; Iukuridze, Eldar (Technology audit and production reserves, 2016)
Number of ice wine companies is increasing every year due to unique chemical composition and consumer demand. Unfortunately, processes associated with outputs of exclusive wines are examined only by Canadian winemakers in scientific literature. Despite of the strict requirements in non-classic technology that largely influence on obtaining of frozen grapes in winter season, other companies and wineries have included ice wine to their product offering. This study surveyed comprehensive information related to first ice wine producers and present definition of rare wine production that are the objectives of current research. Thus, data about primary frozen vintages, wine regions in each producing country and famous winemakers had influenced the expanding of dessert special styles were described; differences in the titles wines were shown. After the experience of the Germans in winter technology, other countries also began to introduce the wine of the premium segment. The current state of production and the wineries, which produce special wine, were reviewed and enterprises developed winter technologies were highlighted in the North America, Europe and Asia. Placement of the wineries, their number and ranges of ice wine were represented and argued according to agro-climatic conditions of each producing lands. The entire world situation referring the existing of ice wine producers in the main regions of European and other territories supplemented special beverages to their profiles suggesting by our study afford an opportunity to fully understand the significant centres of production and changes in wine market supply. Furthermore, current research can conduce to the further publications of ice wine data compositions from different producing areas to evaluating of sensory and physical-chemical parameters and, perhaps, to find the solutions of challenges in ice wine production considering the experiences of each countries.